Peran Karang Taruna dalam Penguatan Keterampilan Sosial Remaja di Desa Bina Baru, Kampar - Kurniawan, Bagas; Jais, Muhammad; Ramadhani, Masytha (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: This study analyzes the role of Karang Taruna, a community youth organization, in strengthening adolescents’ social skills in Bina Baru Village, Kampar Regency, and identifies the forms of social support that sustain its activities. A descriptive qualitative approach was employed with four informants representing the chair and vice-chair of Karang Taruna, a member/community representative, and a community or village representative. Data were collected through interviews, direct observation, and documentation and were analyzed inductively by comparing information across sources and data-collection techniques. The findings reveal four main role patterns. First, religious events, sports, competitions, and village activities provide spaces for positive interaction and encourage adolescents’ participation in public activities. Second, acceptance of differing opinions and closer relationships among members support confidence in communication. Third, communal work and joint activities provide practice in teamwork, caring, and solidarity. Fourth, deliberation and collaboration with families, community members, and village officials are used to address conflict and social problems. The study indicates that Karang Taruna functions as an experiential social-learning space that can support nonformal youth education and the development of practical social skills in rural communities. Abstrak: Penelitian ini bertujuan menganalisis peran Karang Taruna dalam penguatan keterampilan sosial remaja di Desa Bina Baru, Kabupaten Kampar, serta mengidentifikasi bentuk dukungan sosial yang menopang pelaksanaan kegiatannya. Penelitian menggunakan pendekatan kualitatif deskriptif dengan melibatkan empat informan yang mewakili ketua dan wakil ketua Karang Taruna, anggota/masyarakat, serta tokoh masyarakat/perangkat desa. Data diperoleh melalui wawancara, observasi langsung, dan dokumentasi, kemudian dianalisis secara induktif dengan membandingkan informasi antarsumber dan antarteknik pengumpulan data. Temuan menunjukkan empat pola peran utama. Pertama, kegiatan keagamaan, olahraga, perlombaan, dan kegiatan desa menyediakan ruang interaksi positif serta meningkatkan keterlibatan remaja dalam aktivitas publik. Kedua, penerimaan terhadap perbedaan pendapat dan kedekatan antaranggota membantu membangun kepercayaan diri dalam berkomunikasi. Ketiga, gotong royong dan kegiatan bersama melatih kerja tim, kepedulian, dan solidaritas. Keempat, musyawarah serta kolaborasi dengan keluarga, masyarakat, dan perangkat desa digunakan untuk menangani konflik dan permasalahan sosial. Temuan ini menegaskan Karang Taruna sebagai ruang belajar sosial berbasis pengalaman yang relevan bagi pendidikan nonformal remaja di tingkat desa.